Thermoelectric properties of WS2 nanotube networks. (29th November 2016) - Kawai, Hideki; Sugahara, Mitsunari; Okada, Ryotaro; Maniwa, Yutaka; Yomogida, Yohei; Yanagi, Kazuhiro
Abstract: We report the thermoelectric properties of WS2 nanotube networks. By using electrolyte-gating techniques, we turned on a conducting channel in the macroscopic networks of WS2 nanotubes in both the hole and electron regions and evaluated the thermoelectric properties of the networks. We manipulated the P- and N-type Seebeck coefficients in the WS2 nanotube networks by changing the shifts in the gate voltage potentials. The power factor of the WS2 nanotube networks increased as the gate voltage shifted and exhibited a high thermoelectric performance approaching that of single-crystalline WS2 flakes.